Antimicrobial activity of selected Iranian medicinal plants against a broad spectrum of pathogenic and drug multiresistant micro‐organisms. (1st October 2014) - Abedini, A.; Roumy, V.; Mahieux, S.; Gohari, A.; Farimani, M.M.; Rivière, C.; Samaillie, J.; Sahpaz, S.; Bailleul, F.; Neut, C.; Hennebelle, T.
Abstract: The antimicrobial activities of 44 methanolic extracts from different parts of Iranian indigenous plant species used in traditional medicines of Iran were tested against a panel of 35 pathogenic and multiresistant bacteria and 1 yeast. The antimicrobial efficacy was determined using Müller–Hinton agar in Petri dishes seeded by a multiple inoculator and minimal inhibition concentration (MIC) method. The 21 most active extracts (MIC < 0·3 mg ml −1 for one or several micro‐organisms) were submitted to a more refined measurement. The best antibacterial activity was obtained by 10 plants. Microdilution assays allowed to determinate the MIC and MBC of the 21 most active extracts. The lowest achieved MIC value was 78 μ g ml −1, with 4 extracts. This work confirms the antimicrobial activity of assayed plants and suggests further examination to identify the chemical structure of their antimicrobial compounds. Significance and Impact of the Study: This study describes the antimicrobial screening of Iranian plant extracts chosen according to traditional practice against 36 microbial strains, from reference culture collections or recent clinical isolates, and enables to select 4 candidates for further chemical characterization and biological assessment: Dorema ammoniacum, Ferula assa‐foetida, Ferulago contracta (seeds) and Perovskia abrotanoides (aerial parts). This may be useful in the development of potential antimicrobial agents, from easily harvested and highly sustainable plant parts. Moreover, the weak extent of cross‐resistance between plant extracts and antibiotics warrants further research and may promote a strategy based on less potent but time‐trained products.